2006
DOI: 10.1021/bi0523761
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Peptide Inhibitors of the Sarcoplasmic Reticulum Calcium Pump

Abstract: The sequence of phospholamban (PLB) is practically invariant among mammalian species. The hydrophobic transmembrane domain has 10 leucine and 8 isoleucine residues. Two roles have been proposed for the leucines; one subset stabilizes PLB oligomers, while a second subset physically interacts with SERCA. On the basis of the sequence of the PLB transmembrane domain, we chemically synthesized a series of peptides and tested their ability to regulate SERCA in reconstituted membranes. In all, eight peptides were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
66
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(73 citation statements)
references
References 54 publications
6
66
1
Order By: Relevance
“…We have functionally characterized alanine mutants of the C-terminal tail of SLN using co-reconstituted proteoliposomes of SERCA and SLN. We found that Arg 27 and Tyr 31 are essential for SLN function. We also tested the effect of a truncated variant of SLN (Arg 27 stop) and extended chimeras of PLN with the five luminal residues of SLN added to its C terminus.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…We have functionally characterized alanine mutants of the C-terminal tail of SLN using co-reconstituted proteoliposomes of SERCA and SLN. We found that Arg 27 and Tyr 31 are essential for SLN function. We also tested the effect of a truncated variant of SLN (Arg 27 stop) and extended chimeras of PLN with the five luminal residues of SLN added to its C terminus.…”
mentioning
confidence: 75%
“…Nonetheless, key residues in both proteins were found to be important for physical association and function. Notably, mutation of Leu 8 and Asn 11 in SLN resulted in the expected loss of function seen for the comparable Leu 31 and Asn 34 of PLN, and mutation of the predicted phosphorylation site to glutamate (Thr 5 to Glu) appeared to mimic phosphorylation and result in loss of function (17). Although the remaining sampled residues were neutral or loss of function, there are mixed observations on the functional importance of the unique luminal tail of SLN ( Fig.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Residues that contribute to the V max stimulation of SERCA are found in the cytoplasmic and transmembrane domains of PLN (30,36,37). In addition, the transmembrane domain of PLN by itself does not stimulate SERCA activity (40). Presumably then, SERCA interactions and coupling between the cytoplasmic and transmembrane domains of PLN underlie the effect on maximal activity.…”
Section: Discussionmentioning
confidence: 99%